(3JQjGb GdeMHjf aj SjQI SdWGf GdYGQajf CMeO GdQaGYis - (3Jbj GdOjf YHO GdQMef Hf YHO GdeMSf Hf YeQ GdhGSWj GdCfUGQj, YHO GdQMef GdhGSWj,J (B744 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi dG TQjc dg hdG THjg s
(3BNQgG (B:s
(3hgPG BNQ eG GfJgi EdjfG ef efGbH SjOi CMeO GdQaGYi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B98s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B93 s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI ceHQOL (B(99093) s
Keywords: (3GdJGQjNs